Effects of aqueous extract of Neem (Azadirachta indica) leaves as growth promoter and anti-colibacillosis in broilers (Bangladesh Journal of Animal Science, 2014)
The study was conducted to determine the efficacy of aqueous extract of Neem leaves against colibacillosis and as a growth promoter in broilers. A total of 40 commercial day-old broiler chicks were randomly divided into four equal groups; viz. A, B, C and D. Group A was kept as non-treated control, Group B  and C was treated with 1% Neem leaves in drinking water for six weeks,  and colibacillosis was induced at 2nd week in group C and  D. In group D, Neem leaves treatment continued from 2nd to 6th week after the colibacillosis induction to compare its antibacterial efficacy to prophylactic effect. Escherichia coli induction rate was 200µl per bird where 1 ml contains approximately 1X106 CFU (Colony Forming Unit). Data were recorded for live body weight, weekly gain in weight and hematological parameters of birds for six weeks. Clinical examination and antibacterial sensitivity studies  suggests administration of aqueous extract of Neem leaves significantly (p